Neda Mulsant (Coleoptera, Coccinellidae): Redescriptions and revised combinations of two species formerly placed in Cycloneda Crotch - Araújo, Marileusa; de Almeida, Lúcia Massutti (Zootaxa, 2003)
Some species of the genus Cycloneda Crotch (1871) were studied, revised combinations within Neda Mulsant (1850) are made, and illustrations of pertinent characters are provided. Cycloneda callispilota is returned to Neda (= N. callispilota (Guérin-Menéville 1844) comb. rest.), and Cycloneda tredecimsignata is transferred to Neda (= N. tredecimsignata (Mulsant 1850) comb. nov.).